Cerebrovascular Events After a Primary Percutaneous Coronary Intervention Strategy for Acute ST-Segment– Elevation Myocardial Infarction. (April 2015) - Nikolsky, Eugenia; Mehran, Roxana; Dangas, George D.; Xu, Ke; Parvataneni, Rupa; Witzenbichler, Bernhard; Guagliumi, Giulio; Kornowski, Ran; Généreux, Philippe; Brener, Sorin J.; Stone, Gregg W.
<x xml:space="preserve">Abstract</x> Background— Patients with ST-segment–elevation myocardial infarction are at increased risk of cerebrovascular events. We assessed the incidence, predictors, and implications of cerebrovascular events in patients with ST-segment–elevation myocardial infarction managed with a primary percutaneous coronary intervention strategy. Methods and Results— In the Harmonizing Outcomes With Revascularization and Stents in Acute Myocardial Infarction (HORIZONS-AMI) trial, 72 of 3602 patients (2.0%) experienced at least 1 cerebrovascular event (stroke: 63 patients; transient ischemic attack: 12 patients) during the 3-year follow-up (40.3% within 30 days, 20.8% between 30 days and 1 year, and 38.9% between 1 and 3 years). Stroke was ischemic in 58 (92.1%) patients and hemorrhagic in 5 (7.9%) patients. More than half of all strokes (52.3%) were disabling. By principal management strategy, cerebrovascular events developed in 2.0%, 14.9%, and 1.9% of patients triaged to primary percutaneous coronary intervention, coronary artery bypass grafting, and medical therapy, respectively (P<0.0001). Cerebrovascular events were independently predicted by older age, creatinine clearance <60 mL/min, treatment with coronary artery bypass grafting, anemia, and diabetes mellitus. Cerebrovascular events were associated with significantly increased rates of 3-year mortality (20.5% versus 6.5%; P<0.0001), as well as reinfarction (14.3% versus 3.8%; P=0.0007), ischemia-driven target vessel revascularization (22.8% versus 13.0%; P=0.006), and major bleeding (23.5% versus 8.4%; P<0.0001). Conclusions— In HORIZONS-AMI, cerebrovascular events within 3 years after ST-segment–elevation myocardial infarction in patients undergoing a primary percutaneous coronary intervention management strategy occurred in 2.0% of patients and were most frequent after coronary artery bypass grafting. Cerebrovascular events were often disabling and were strongly associated with high rates of death, reinfarction, recurrent ischemia, and major bleeding. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00433966.